Sertindole-Induced Hypomania: A Case Report - Atmaca, Murad; Kanmaz, Ebru (Kure Iletisim Grubu A S, 2008)
Although atypical antipsychotics are now commonly used in the treatment of bipolar disorder, they can also lead to manic and hypomanic states. Here, we report a case of hypomanic episode due to initiation of sertindole treatment in a male patient diagnosed with schizophrenia.
Keywords: Sertindole; hypomania; case